UNDERGRADUATE STUDENTS’ PERCEPTIONS TOWARDS LECTURER’S CLASSROOM MANAGEMENT IN THE INDONESIAN TERTIARY CONTEXT - Andi Asri Jumiaty; Heri Kuswoyo (Linguistics and Literature Students' Journal, 2023)
This study was aimed at investigating the perceptions of students at lecturer’s classroom management in teaching English. This research employed a descriptive method. The population of this study was twenty undergraduate students in the second semester of reading class in the 2017/2018 academic year conducted at one of university in Makassar, Indonesia. The sample was selected using a purposive sampling. The data were collected through questionnaires and analyzed using a Likert scale. The results showed that the second-year students agreed and categorized high on teacher’s classroom management in learning English. By showing consistent reports, an effective classroom manager meets students’ need. The results also offered overwhelming benefits for students and lecturer, namely (1) the lecturer can build good interaction with the students, (2) the lecturer can create fun atmosphere in the classroom, (3) it can help students to improve their skills, if the lecturer has an appropriate method, and (4) the lecturer can find out new strategy how to teach English well. These results provide further evidence for examining students’ perception towards lecturer’s classroom management is helpful for lecturers and students at reading classroom where English is used as a foreign language.